Naturally derived efflux pump inhibitor among tetracycline-resistant Acinetobacter baumannii isolates - Ruqaya Kareem Abass Al-ammery; Zainab Adil Ghani Chabuck (Medical Journal of Babylon)
Abstract Background: The antimicrobial resistance of Acinetobacter baumannii is of major concern. It is one of the commonly distributed nosocomial pathogens, and its strains are frequently reported to demonstrate resistance to the most routinely prescribed antibiotics in varying degrees. Objective: This study aimed to detect the inhibitory effect of chamomile extract against the efflux pump of A. baumannii. Materials and Methods: Clinical samples (125) were collected from different sites (urine, sputum, wound, and burn swabs), followed by A. baumannii isolation and identification, and detection of tetracycline susceptibility test by disk-diffusion. Later on bacterial efflux pump activity was detected by ethidium bromide cartwheel assay and water extract of chamomile was used as an inhibitor of efflux pump A. baumannii. Results: The percentage of A. baumannii isolation 23/125 (18.4%) that distributed as 25% isolates were obtained from sputum, 17.9% isolates from burns, whereas 16% and 12.5% isolates from urine and wounds respectively. It showed various resistances against different members of the three generations of tetracyclines, with the highest resistance against minocycline 47.8% followed by resistance to tetracycline and doxycycline as 43.5% and 39%, respectively. Efflux pump was detected in all cases, water extract of chamomile showed a significant inhibitory effect especially at 80 mg/mL concentration. Conclusion: Efflux pump is an important mechanism for tetracycline resistance among A. baumannii isolates, and the watery extract of chamomile can be considered a prompt inhibitor for this pump.